Aspirin Eugenol Ester Protects Vascular Endothelium From Oxidative Injury by the Apoptosis Signal Regulating Kinase-1 Pathway - Huang, Mei-Zhou; Zhang, Zhen-Dong; Yang, Ya-Jun; Liu, Xi-Wang; Qin, Zhe; Li, Jian-Yong (Frontiers in Pharmacology, 2020)
Aspirin eugenol ester (AEE) is a new potential pharmaceutical compound possessing anti-inflammatory, anti-cardiovascular disease, and anti-oxidative stress pharmacological activity. These pharmacological activities of AEE are party dependent on its regulation of cell apoptosis. However, it is still unclear how AEE reduces cell apoptosis on the basis of its anti-oxidative stress effect. The present study aimed to reveal the vascular anti-oxidative mechanism of AEE with the help of H2O2-induced oxidative stress in HUVECs and paraquat-induced oxidative stress in rats. Among different intervention groups of HUVECs and rats, the expression of ASK1, ERK1/2, SAPK/JNK, and p38, and the phosphorylation level of ERK1/2, SAPK/JNK, and p38 were detected. To probe the effect of ASK1 and ERK1/2 on the anti-apoptosis activity of AEE in the oxidative stress model, the corresponding inhibitors of ASK1 and ERK1/2 were applied. The results showed that, in the HUVECs, 200 μM H2O2 treatment significantly increased the phosphorylation of SAPK/JNK and level of ASK1, but decreased the phosphorylation of ERK1/2, while pre-treating HUVECs with AEE could significantly ameliorate the aforementioned H2O2-induced changes. The findings were seen in vitro and in vivo. Moreover, inhibition of ASK1 and ERK1/2 showed that ASK1 plays a vital role in the protective effect of AEE on H2O2-induced apoptosis. All findings suggested that AEE protected vascular endothelium from oxidative injury via mediating the ASK1 pathway.